2004
DOI: 10.1016/j.rfe.2004.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency and the conduct of European banks: Developments after 1992

Abstract: This paper addresses the efficiency of the European banking sector in the five-year period following the implementation of the Second Banking Directive of the European Union (EU).We first determine the degree of cost efficiency of EU banks in the period 1993-1997. After that we explore to what extent efficient European banks are managed differently than their inefficient peers. Our datasets comprise 5 years of observations on 1347 savings banks and 873 commercial banks, and we use the new Recursive Thick Front… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 49 publications
(36 reference statements)
2
40
0
2
Order By: Relevance
“…It is also expected to capture the implications for bank efficiency stemming from operating in different economic environment, as demand for financial products depends on the level of economic activity. Empirical studies tend to find that countries with relatively high GDP growth are characterised by more efficient banking institutions (e.g., Demirguc-Kunt and Maksimovic, 1998;Schure et al, 2004;Yildirim and Philippatos, 2007). Yearly dummy variables are included to control for time effects.…”
Section: Asian Journal Of Finance and Accountingmentioning
confidence: 99%
“…It is also expected to capture the implications for bank efficiency stemming from operating in different economic environment, as demand for financial products depends on the level of economic activity. Empirical studies tend to find that countries with relatively high GDP growth are characterised by more efficient banking institutions (e.g., Demirguc-Kunt and Maksimovic, 1998;Schure et al, 2004;Yildirim and Philippatos, 2007). Yearly dummy variables are included to control for time effects.…”
Section: Asian Journal Of Finance and Accountingmentioning
confidence: 99%
“…In the study by Schure, Wagenvoort and O'Brien (2004) on the productivity of the European banking sector for the period 1993-1997, the Italian and the Spanish banks were found to be the least efficient. On the other hand, Casu, Girardone and Molyneux (2004) found that Italian banks had an 8.9% productivity increase; Spanish banks had a 9.5% increase, while German, French and English banks had 1.8%, 0.6% and 0.1% productivity increase, respectively over the period 1994-2000.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Most studies on banks' efficiency (Altunbas¸, Gardener, Molyneux, and Moore, 2001;Berger, 1995;Berger and Humphrey, 1997;Berger and Mester, 1997;Bos and Schmiedel, 2007;Goddard, Molyneux, and Wilson, 2001;Maudos, Pastor, Pérez, and Quesada, 2002;Schure, Wagenvoort, and O'Brien, 2004;Williams, Peypoch and Barros, 2009) focus on the US and Europe and neglect banks in emerging countries such as Nigeria. Multi-country analysis usually considers factors such as legal tradition, accounting conventions, regulatory structures, property rights, culture and religion as possible explanations for cross-border variations in financial development and economic growth (Beck, Demirgüc¸-K, and Levine, 2003;Beck and Levine, 2004;La Porta, Lopez-de-Silanes, Shleifer, and Vishny, 1997;Levine, 2003;Stulz and Williamson, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In general, the extensive empirical evidence does not provide conclusive proof that bank performance is explained by either concentrated market structures and collusive price-setting behaviour or superior management and production techniques. Bank performance levels are found to vary widely across banks and banking sectors (Altunbas¸ et al, 2001;Maudos et al, 2002;Schure et al, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%